Solar Modulation of AMS-02 Daily Proton and Helium Fluxes with Modified Force-field Approximation Models - Cheng-Rui Zhu; Mei-Juan Wang (The Astrophysical Journal)
As galactic cosmic rays (GCRs) propagate through the turbulent plasma environment within the heliosphere, they undergo a process of diffusion, drift, and energy loss, leading to a notable reduction in their flux. This is the solar modulation impact. Recently, the cosmic-ray experiment AMS-02 published daily fluxes of proton and helium for the period from 2011 May 20 to 2019 October 29 in the rigidity interval from about 1 to 100 GV, exhibiting fine time structures that correlate with solar wind properties on a daily basis. In this work, we employ three different modified force field approximation models to fit the data. By fitting to the daily proton and helium fluxes, we get the time series of solar modulation potential. We find good agreement of data and model predictions for both proton and helium with the same parameters in two modified force field approximation models. The results in this study verify that the modified force-field approximation model is a valid parameterization of the GCR spectrum also at daily timescales.